<span> -3x^2 y +4x
</span><span> =-3(-4)^2 (2) + 4(-4)
=-96-16
=-112</span>
Answer:
y = 5x + 2 . . . . . . . . . . (1)
3x = -y + 10 . . . . . . . . (2)
3x = -(5x + 2) + 10
3x = -5x - 2 + 10
3x + 5x = -2 + 10
8x = 8
x = 1
y = 5(1) + 2 = 5 + 2 = 7
Solution is (1, 7) The answer is (1,7)
Step-by-step explanation:
Answer:
See below
Step-by-step explanation:
15)
In the right-angle triangle, once one of the angles is 44º, then, the unknown angle is
.
![180 = 44 + 90 + x](https://tex.z-dn.net/?f=180%20%3D%2044%20%2B%2090%20%2B%20x)
![180 = 134 + x](https://tex.z-dn.net/?f=180%20%3D%20134%20%2B%20x)
![x= 46](https://tex.z-dn.net/?f=x%3D%2046)
The angle
of the other triangle plus the angle
of the right-angle triangle is equal to 90º, therefore they are complementary angles.
So,
![90 = x + y](https://tex.z-dn.net/?f=90%20%3D%20x%20%2B%20y)
![90 = 46 + y](https://tex.z-dn.net/?f=90%20%3D%2046%20%2B%20y)
![y=44](https://tex.z-dn.net/?f=y%3D44)
To find ?, we have
![180 = 58 + 44 +?](https://tex.z-dn.net/?f=180%20%3D%2058%20%2B%2044%20%2B%3F)
![180 = 58 + 44 +?](https://tex.z-dn.net/?f=180%20%3D%2058%20%2B%2044%20%2B%3F)
![? =78](https://tex.z-dn.net/?f=%3F%20%3D78)
16)
The sum of the internal angles of the triangle with angles 50º and 25º is equal to 180º, therefore, the other angle is
![180 = x + 50 + 25\\180 = x+ 75\\x=105](https://tex.z-dn.net/?f=180%20%3D%20x%20%2B%2050%20%2B%2025%5C%5C180%20%3D%20x%2B%2075%5C%5Cx%3D105)
Once the angles are opposite, they are the same. For the triangle with the 36º angle, we have
![180 = 36 + 105 + y](https://tex.z-dn.net/?f=180%20%3D%2036%20%2B%20105%20%2B%20y)
![180 = 141+ y](https://tex.z-dn.net/?f=180%20%3D%20141%2B%20y)
![y=39](https://tex.z-dn.net/?f=y%3D39)
![?=39](https://tex.z-dn.net/?f=%3F%3D39)
we know that
If square GYTD is translated
units left and
units up to produce square G'Y'T'D'
that means
the rule of transformation is
![(x,y)-------> (x-2,y+2)](https://tex.z-dn.net/?f=%28x%2Cy%29-------%3E%20%28x-2%2Cy%2B2%29)
<u>Find the coordinates of the image</u>
![G (-4,3)------->G'(-4-2,3+2)=G'(-6,5)](https://tex.z-dn.net/?f=G%20%28-4%2C3%29-------%3EG%27%28-4-2%2C3%2B2%29%3DG%27%28-6%2C5%29)
![Y (0,3)------->Y'(0-2,3+2)=Y'(-2,5)](https://tex.z-dn.net/?f=Y%20%280%2C3%29-------%3EY%27%280-2%2C3%2B2%29%3DY%27%28-2%2C5%29)
![T (0,-1)------->T'(0-2,-1+2)=T'(-2,1)](https://tex.z-dn.net/?f=T%20%280%2C-1%29-------%3ET%27%280-2%2C-1%2B2%29%3DT%27%28-2%2C1%29)
![D (-4,-1)------->D'(-4-2,-1+2)=D'(-6,1)](https://tex.z-dn.net/?f=D%20%28-4%2C-1%29-------%3ED%27%28-4-2%2C-1%2B2%29%3DD%27%28-6%2C1%29)
therefore
<u>the answer is the option</u>
G'(−6, 5), Y'(−2, 5), T'(−2, 1) , and D′(−6, 1)
Answer: W gives the weight of a puppy, in pounds, as a
function of its age, t, in months.
Step-by-step explanation: